Pengaruh Latihan Circuit Training Terhadap Kecepatan Lari Sprint 50 Meter Pada Siswa SMP Negeri 12 Kota Bengkulu - Syari Ramadan; Deffri Anggara; Dwingki Marta Putra (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to examine the effect of circuit training on 50-meter sprint speed in students at SMP Negeri 12, Bengkulu City. This research is quantitative. The sample size was 30. The instrument used in this study was 50-meter sprint speed. The results of circuit training on 50-meter sprint speed in students at SMP Negeri 12, Bengkulu City, obtained a positive correlation of 0.86, meaning that the higher the score, the stronger the relationship between the two variables. It can be further concluded that circuit training has an effect on 50-meter sprint speed in students at SMP Negeri 12, Bengkulu City.